A taste of wellness: UiTM & KPJ collaborate to celebrate fermented foods - Wan Ismail, Wan Nordini Hasnor; Zulkifli, Muhammad Faiz (Faculty of Pharmacy, 2025)
On 18th May 2025, the Faculty of Pharmacy, Universiti Teknologi MARA (UiTM) Cawangan Pulau Pinang, Kampus Bertam, in collaboration with KPJ Healthcare College, Penang, successfully organized a joint educational event titled FermentFest: The Probiotic Playground. Spearheaded by the student council, the Society of Pharmacy Students (SOPHYS) UiTM Cawangan Pulau Pinang (Bertam Campus), the program aimed to raise awareness and deepen students' understanding of the benefits of fermented foods on gut health and overall well-being.